Strategy to Reduce the Incidence of Pulmonary Tuberculosis (TB) Through Spatial Analysis and Literacy Studies in Batang Regency, Indonesia - Irawan, Teguh; Wahyuningsih (Open Access Indonesian Journal of Medical Reviews, 2023)
Every year, around 2 million people in the world die from TB, and 9 million become infected with TB. Indonesia is located in position third after India and China. Batang Regency is one of the locations with a high prevalence of TB in Central Java. In 2021, there were 840 TB cases recorded in Batang Regency, increasing sharply in 2022 to 1192 cases. Seeing this trend, it is necessary to carry out research on strategies to reduce the incidence of pulmonary TB using literacy studies and spatial analysis in Batang Regency, Indonesia, in 2023. This study is a descriptive study using spatial analysis. This research is accompanied by an in-depth look at answers to TB program holders at the Batang Regency Health Service. The subjects in this study were patients with pulmonary TB in Batang Regency. The data analysis used the ArcView GIS program to obtain a map of the distribution of pulmonary TB cases in Batang Regency. Research results show that there were 831 pulmonary TB cases in 2020, 840 cases in 2021, and a sharp increase in 2022 with 1192 cases. The highest number of cases was in Batang District, with 279 cases, followed by Warungasem District, with 123 cases, and Bandar District, with 111 cases. These three districts are lowland and densely populated areas. Therefore, the Batang Regency Health Service needs to prioritize TB control programs in areas with the most cases.